Evoluzione della scienza e giudizio di rimproverabilità per colpa Verso una nuova tipicità del crimen culposum - Valbonesi, Cecilia (Premio Ricerca «Città di Firenze», 2014)
The growing complexity of production phenomena is causing a progressive expansion of culpable liability assumptions. In particular, the jurisprudence dealing with long-term diseases bases the culpable reproach on scientific knowledge gained in a later period, thus operating a destructuring of the constitutive profiles of the crimen culposum. The work intends to investigate the complex relationship between guilt and scientific progress, highlighting the continuous dialogue between doctrine and jurisprudence, with particular attention to the implications of risk criminal law and precautionism. The search for a new typicality of culpable reproach does not ignore the recent legislative developments aimed at giving meaning to guidelines and protocols.